Institutional Investors and Asset Pricing in Emerging Markets - Buckberg, Elaine (IMF Working Papers; Working Paper ;, 1996)
This paper presents a new theory of asset pricing intended to address why other developing country equity markets responded so strongly to the Mexican devaluation, while the world's major stock markets were unmoved. This phenomenon can be explained if investors follow a two-step portfolio allocation process, first determining what share of their portfolio to invest in developing countries, then allocating those funds across the emerging markets. For 12 of 13 markets studied, the one-factor CAPM is rejected in favor of a two-factor asset pricing model, including both a broad emerging markets portfolio and the global market portfolio.